Ferulic Hydroxamic Acid Triazole Hybrids as Peptide Deformylase Inhibitors: Synthesis, Molecular Modelling and Biological Evaluation. Issue 37 (1st October 2020) - Aneja, Babita; Khan, Parvez; Alam, Shadab; Hasan, Phool; Abid, Mohammad
Abstract: Design and development of peptide deformylase (PDF) inhibitors has gained attention as it is a highly conserved and specific enzyme for bacterial protein synthesis. This makes it a specific and attractive drug target. Therefore, based on the targeted drug‐discovery approach, a series of ferulic acid‐based nonpeptidic hydroxamic acid‐triazole hybrids was synthesized. All the semi‐synthetic compounds (8 a –p ) were evaluated against a panel of Gram‐positive and Gram‐negative bacterial strains. Most of the compounds showed antibacterial activities against S. pneumoniae while few were active against E. coli . Among all, the compound 8 j showed strong potency against S. pneumoniae with IC50 value 34.57 μg/mL whereas for E. coli the observed IC50 was 66.20 μg/mL. Growth kinetics study showed the bacteriostatic nature of compound 8 j against S. pneumoniae . Interestingly, in the studied concentration range, no significant hemolysis or cytotoxicity was observed towards human cells, suggesting the non‐toxic nature of compound 8 j . Molecular docking studies showed that compound 8 j occupies the same active site where actinonin (a known inhibitor of PDF) binds and it also mimics the mode of interactions by offering significant interactions with the corresponding amino acid residues of PDF. The outcome of this study suggested the potential implications of the present scaffold for the development of antibacterial molecules targeting PDF. Abstract : Ferulic acid was identified with little affinity towards bacterial peptide deformylase, a potential drug target for antibacterial drug development. Different ferulic hydroxamic acid‐triazole hybrid molecules were synthesized and screened for activity. Comparative studies including molecular docking give insights into the mode of interaction and enhanced activity of ferulic hydroxamic acid‐triazole hybrid.